We need collaboration and co-creation to address challenges facing coastal communities - Raha, Debadayita; Davies-Vollum, Katherine Sian; Hemstock, Sarah L.; Boateng, Isaac; Islam, Md Tariqul; Pierce, Charles A. E. (Springer, 2024)
Coastal communities across the globe are faced with multifaceted, interconnected challenges with competing environmental, social and economic needs. In rural coastal communities of the Global South, the challenges presented by climate change are complicated by those related to development, resource management and sustainable livelihoods. The rapid growth of such coastal communities exacerbates these challenges and reinforces the need for effective and sustainable governance. Such governance requires a move from top-down approaches to human-centred approaches. Human-centred coastal governance engages multiple stakeholders and combines multidisciplinary knowledge, participatory approaches, co-creation of solutions and multi-institutional partnerships. Here we present case studies from coastal communities in Vanuatu, Ghana and Bangladesh. These illustrate several of the complex challenges facing such communities and the collaborative and empowering strategies that have been used to meet them. Based on these case studies, we present a transdisciplinary framework to inform the co-creation of coastal management strategies that meet interconnected human and environmental needs.
Keywords: Climate-change impacts; Climate-change policy; Environmental studies; Sustainability